Kitāb Kināyāt al-udabāʾ wa-išārāt al-bulaġāʾ - Ǧurǧānī, Aḥmad Ibn-Muḥammad al- -1089; Ṯaʿālibī, ʿAbd-al-Malik Ibn-Muḥammad aṯ- 961-1038 (ad-Dār al-Mutawasiṭīya lin-Našr, 2018)
Arabic language; figures of speech; early works to 1800
Keywords: Arabic language / Figures of speech / Early works to 1800; Arabic language / Figures of speech; Sprache; Arabisch; Rhetorische Figur